Physical activity and affective and aggressive tendencies in adolescents: Pedagogical-psychological perspective of emotional and aggressive responses regulation - Zheng, Qianwen; Kasmalieva Anarkhan; Li , Jianghua (Environment and Social Psychology, 2025)
In this paper, the author will discuss the effects of regular physical activity on the control of aggression among adolescents on pedagogical and psychological levels. It examines the influence of the various types of exercises, exercise frequencies, and school based programs on emotional awareness, self-control, and peer conflict. The debate incorporates the data taken in experiments, longitudinal studies, and classroom interventions. The physiological regulation of stress and mood enhancement is achieved by aerobic exercise. The team sports develop social abilities and give systematic environments to handle impulses. Yoga and tai chi are mind-body practices, which make individuals more focused and less emotional. The paper includes also the practical recommendations to schools, addressing the exercise intensity in relation to age, in accordance with social-emotional learning, teacher education, and regular follow-up. The paper identify common methodological limitations in current research, including short follow-up periods, inconsistent aggression measures, and limited attention to gender and socio-economic differences. The article concludes with actionable recommendations for educators and researchers, a proposed evaluation toolkit you can adopt, and a curated reference list of 30 to 35 accessible empirical and review sources. This work aims to help you design evidence-based physical activity programs that reliably improve emotional regulation and reduce adolescent aggression, and to meet the reporting standards required by English for Specific Purposes journals.